2018
DOI: 10.17116/neiro2018823112
|View full text |Cite
|
Sign up to set email alerts
|

The role of lipid metabolism disorders, atypical isoforms of protein kinase C, and mutational status of cytosolic and mitochondrial forms of isocitrate dehydrogenase in carcinogenesis of glial tumors

Abstract: The relationship between molecular genetic and metabolic disorders is one of the challenges of modern oncology. In this review, we consider lipid metabolism and its changes as one of the factors of oncogenesis of glial tumors. Also, we demonstrate that the genome and the metabolome are interconnected by a large number of links, and the metabolic pathways, during their reorganization, are able to drastically affect the genetic structure of the cell and, in particular, cause its tumor transformation. Our own obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 79 publications
1
1
0
Order By: Relevance
“…Recent studies revealed that lipid metabolism disorders are important in carcinogenesis and cancer development, as they induce abnormalities in the expression of various genes and proteins, and in the regulation of cytokines and signaling pathways (17,18). The present study demonstrated that lipid metabolism disorders occurred in patients with TC.…”
Section: Discussionsupporting
confidence: 59%
“…Recent studies revealed that lipid metabolism disorders are important in carcinogenesis and cancer development, as they induce abnormalities in the expression of various genes and proteins, and in the regulation of cytokines and signaling pathways (17,18). The present study demonstrated that lipid metabolism disorders occurred in patients with TC.…”
Section: Discussionsupporting
confidence: 59%
“…Many studies focus on the relationship between abnormal blood lipid metabolism and cancer. Recent studies have revealed that lipid metabolism disorders occur in carcinogenesis and the development of cancer, as cancer induces abnormalities in the expression of various genes and proteins, as well as in the regulation of cytokines and signaling pathways [21,22]. A study by Li et al found that the TC levels were signi cantly different between patients with thyroid cancer and control groups, and a disordered lipid pro le occurred in patients with thyroid cancer [2].…”
Section: Discussionmentioning
confidence: 99%